The date - Jensen, Louise (Grand Central Publishing, 2019)
Saturday night: Recently separated from her husband, Ali has been persuaded by her friends to go on a date with a new man. Sunday morning: Ali wakes up at home: she is alone, she is hurt, and she has no memory of what happened to her. Worse still, when she looks in the mirror, Ali doesn't recognize the face staring back at her. She can't recognize her friends and family. And she can't recognize the person who is trying to destroy her. -- adapted from back cover